Migration museums as catalysts for local and migrant interaction - Çakırer Özservet, Yasemin; Koçak, Berk (Mersin University, 2024)
This study explores the role of immigration museums in promoting social cohesion between local communities and immigrants. Immigration movements are an ongoing feature of current global dynamics and influence the cultural and artistic spheres. Integrating immigrants into local societies has become a core goal of nation-states and requires innovative approaches. Traditionally viewed as repositories of cultural artifacts, museums have evolved into dynamic spaces that promote cultural interaction and mutual understanding. This study focuses on immigration museums in Germany, Poland, Brazil, and Türkiye, exploring how these institutions contribute to social peace by documenting migration processes and facilitating contact between immigrants and natives. The study uses a situational description approach to conduct a case study of the Immigration Museum and its activities. These museums actively combat bias, promote empathy, and foster community through exhibits, educational programs, and interactive demonstrations. The findings highlight the importance of immigration museums in bridging cultural gaps and strengthening social cohesion. These museums help create inclusive societies that respect and value diverse backgrounds by providing spaces for cultural exchange. The research highlights the transformative potential of contemporary museology to address the complexities of migration and integration and provides valuable insights for policymakers and cultural practitioners.
Keywords: Museology; Migration Museums; Social Cohesion; Encounter Places; Cultural Integration